STUDI LITERATUR: PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN KONTEKSTUAL TERHADAP PEMAHAMAN OPERASI HITUNG CAMPURAN SISWA SEKOLAH DASAR - Yunita Lestari; Ratna kholifatul; Sulis Wahyu Ningsih; Azamul Fadhly Noor Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Elementary school students’ understanding of mixed arithmetic operations remains a challenge in mathematics learning. One effort to address this issue is through the use of contextual learning media that connect mathematical content with real-life situations and students’ everyday experiences. This study aims to examine the effect of contextual learning media on elementary school students’ understanding of mixed arithmetic operations through a literature study. The method employed was a literature review by analyzing various scientific sources, including journal articles, books, and relevant research findings published within a certain period. The results of the review indicate that the use of contextual learning media improves students’ conceptual understanding of mixed arithmetic operations, helps students relate abstract concepts to real-world situations, and enhances students’ learning motivation and active participation. In addition, contextual media contribute to reducing conceptual errors and improving mathematics learning outcomes. Based on the findings of the literature review, it can be concluded that contextual learning media have a positive and significant effect on elementary school students’ understanding of mixed arithmetic operations and are therefore recommended for optimal implementation in elementary school mathematics learning. Keywords: Contextual Learning Media, Mixed Arithmetic Operations, Conceptual Understanding, Mathematics